The mexican Frankliniella desertileonidum species assemblage, in the "Intonsa Group" (Insecta, Thysanoptera: Thripidae) - Johansen, Roberto M. (Instituto de Ecología, A.C., 1998)
The review of the Mexican Neovolcanic species Frankliniella desertíleonidum Watson was carry out herein, based in a Paratype, as well as new material. This allowed the reconsideraron of F. oneillae Johansen from the Sierra Madre Oriental, as a different and valid species, with respect to F. desertíleonidum. This supported the determination of three new more species from the Sierra Madre Oriental. All these elements derivad in the stablishment of relationships supported with shared morphologic characters between the five species. This allowed the grouping in a specífic assemblage. Morphologic illustrations of the head, antennae, thorax and abdomen of all the species, are included.